Practical guidelines on endoscopic treatment for Crohn's disease strictures: a consensus statement from the Global Interventional Inflammatory Bowel Disease Group. (April 2020) - Shen, Bo; Kochhar, Gursimran; Navaneethan, Udayakumar; Farraye, Francis A; Schwartz, David A; Iacucci, Marietta; Bernstein, Charles N; Dryden, Gerald; Cross, Raymond; Bruining, David H; Kobayashi, Taku; Lukas, Martin; et al.
Summary: Stricture formation is a common complication of Crohn's disease, resulting from the disease process, surgery, or drugs. Endoscopic balloon dilation has an important role in the management of strictures, with emerging techniques, such as endoscopic electroincision and stenting, showing promising results. The underlying disease process, altered bowel anatomy from disease or surgery, and concurrent use of immunosuppressive drugs can make endoscopic procedures more challenging. There is an urgent need for the standardisation of endoscopic procedures and peri-procedural management strategies. On the basis of an extensive literature review and the clinical experience of the consensus group, which consisted of representatives from the Interventional Inflammatory Bowel Disease Group, we propose detailed guidance on all aspects of the principles and techniques for endoscopic procedures in the treatment of inflammatory bowel disease-associated strictures.